Determination of fatty acid profile of branded and unbranded processed foods commonly available in the Indian market with special reference to trans fatty acids: DETERMINATION OF FATTY ACID PROFILE OF BRANDED AND UNBRANDED PROCESSED FOODS - S GEETHA; K MANORAMA; APARNA KUNA; CH JAGAN (Journal of Oilseeds Research, 2016)
Adverse health effects from the consumption of trans fatty acids (TFA) have led to efforts to decrease the consumption of foods containing these lipids. There is a need for up to date information on TFA levels in foods to support decision-making by regulators on labelling and health claims. In this context, the present study provides detailed information about the fatty acid profile with special reference to TFA of selected branded and unbranded Indian processed foods. Products were analysed for fatty acid composition by using GC. Results showed that the amount of TFA, SFA, MUFA and PUFA varied considerably among the analyzed samples. Among the products analyzed, vanaspati showed highest fat content, chocos showed highest SFA content (82%), boondi showed highest UFA content (74%) and cake showed highest TFA. The major trans forms in all samples were elaidic acid and linolelaidic acid (C18:2, trans-6). Vaccenic acid was detected only in health drinks (0.33%). Six out of 15 product labels were misrepresenting the TFA content. Stringent regulations are required for reducing TFA content of commonly consumed foods in India.